The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.20873/jbb.uft.cemaf.v4n4.oliveira
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética entre acessos de mentrasto do Estado do Tocantins através de marcadores RAPD

Abstract: Ageratum conyzoides (Asteraceae) is known in Brazil for its medicinal properties being mainly used as painkiller and anti-inflammatory. Due to the existence of few genetic studies for this species, this work aimed to characterize the genetic diversity among nine accessions from different sites at Tocantins state, to provide information about its genetic resources. Similarity coefficients obtained varied from 48% to 80%, result of amplification of 102 fragments, of which 72 (70.5%) were polymorphic. Groupment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Leite et al (2016) analyzed 27 early soybean genotypes in Currais, PI, Brazil, and reported a similar CV of 10.15% for PHM. Andrade et al ( 2016) studied F 6 generation soy strains in Jaboticabal, SP, Brazil, and obtained higher CV estimates for a number of branches (69.5%), whereas Oliveira et al (2019), studying the genetic diversity of soy strains developed by the genetic improvement program of the Federal University of Tocantins aiming at biodiesel production, reported CVs ranging from 2.5 to 28.2% for the agronomic characters evaluated.…”
Section: 1mentioning
confidence: 99%
“…Leite et al (2016) analyzed 27 early soybean genotypes in Currais, PI, Brazil, and reported a similar CV of 10.15% for PHM. Andrade et al ( 2016) studied F 6 generation soy strains in Jaboticabal, SP, Brazil, and obtained higher CV estimates for a number of branches (69.5%), whereas Oliveira et al (2019), studying the genetic diversity of soy strains developed by the genetic improvement program of the Federal University of Tocantins aiming at biodiesel production, reported CVs ranging from 2.5 to 28.2% for the agronomic characters evaluated.…”
Section: 1mentioning
confidence: 99%
“…A Krisnawati e Adie (2019), analisaram a variabilidade genética de soja para a resistência da quebra de vagens. Outros estudos relacionados a produção de biodiesel (OLIVEIRA et al 2019), morfometria reprodutiva (COSTA et al, 2018, tolerância de brotação pré-colheita (KUMAR et al, 2021) e aspetos fitossanitários e nutricionais (LORO et al, 2021).…”
Section: Diversidade Genética Aplicada Ao Melhoramento De Sojaunclassified